1985
DOI: 10.1039/dt9850001213
|View full text |Cite
|
Sign up to set email alerts
|

A mechanistic study on complexes of type mer-[Cr(CO)32-L–L)(σ-L–L)](where L–L = Ph2PCH2PPh2, Ph2PNHPPh2, or Ph2PNMePPh2) using spectroscopic and convolutive electrochemical techniques

Abstract: The new complexes rner-[Cr(CO),(q'-L-L) (0-L-L)] [where L-L = Ph,PCH,PPh, (dppm), Ph,P-NHPPh, (dppa) or Ph,PNMePPh, (dppma)] were synthesized by treating [Cr(CO),(C,H,)] (C,H, = cyclohepta-l,3,5-triene) with the appropriate diphosphine. The complexes were characterized by i.r. and by 31P-{1H} and "H-{,lP} n.m.r. spectroscopy. The electrochemical and chemical oxidation of these complexes was investigated and the products identified by electrochemical techniques and by e.s.r. and i.r. spectroscopy. The one-elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 2 publications
1
28
0
Order By: Relevance
“…On the other hand, when α = 0.3 the values of Ψ cover the range 0.130 -4.04x10 -5 in case of variation ∆E p from 217. 4 It was found that the value of the heterogeneous rate constant (k s ) of Pb 2+ ion in 0.1M KNO 3 calculated from the working curve established in this work equals (2.25x10 -2 cm.s -1 ) which compare well with the value (2.10x10 -2 cm.s -1 ) reported in literature 10 confirming the accuracy of our method. Also the value of k s for the system Fe 3+ / Fe 2+ calculated in this work (3.41x10 -4 cm.s -1 ) compare well with the value established in literature (3.0 x 10 -4 cm.s -1 ).…”
Section: Methodssupporting
confidence: 79%
See 1 more Smart Citation
“…On the other hand, when α = 0.3 the values of Ψ cover the range 0.130 -4.04x10 -5 in case of variation ∆E p from 217. 4 It was found that the value of the heterogeneous rate constant (k s ) of Pb 2+ ion in 0.1M KNO 3 calculated from the working curve established in this work equals (2.25x10 -2 cm.s -1 ) which compare well with the value (2.10x10 -2 cm.s -1 ) reported in literature 10 confirming the accuracy of our method. Also the value of k s for the system Fe 3+ / Fe 2+ calculated in this work (3.41x10 -4 cm.s -1 ) compare well with the value established in literature (3.0 x 10 -4 cm.s -1 ).…”
Section: Methodssupporting
confidence: 79%
“…[2][3][4][5][6][7] The electrochemical parameters used for generating the theoretical cyclic voltammograms of the electrochemical reaction …”
Section: Introductionmentioning
confidence: 99%
“…EC mechanism, the backward direction of I 1 convolution does not return to the initial value. 30 On the other hand, in case of a reversible chemical reaction preceeding charge transfer, i.e. CE mechanism, the limiting convoluting current I lim does not produce the plateau value at low scan rate, Fig It was found that, the values of cathodic peak potential, E pc shift towards more cathodic values, with increasing the sweep rate, also, the peak separation (ΔE p ) values increase with increasing the sweep rate.…”
Section: Results and Discussion Cyclic Voltammetrymentioning
confidence: 98%
“…[24][25][26][27] The shape of the I 1 -E curve exhibit important feature for the identification of the nature of the electrode process. For a simple rapid charge transfer, the shape of The convolution of the current data with an inverse square root of time, I 1 is defined as: [24][25][26][27][28][29][30] ( 2) where I 1 is the convoluted current at the total elapsed time and i(u) is the experimental current at time u.…”
Section: Convolutive Voltammetrymentioning
confidence: 99%
“…Convolution and deconvolution procedures were carried out according to the method described earlier (10). The convolution logarithmic analysis was carried out on the basis of the following general equations ' and ~r e s h stock solution of tetraethylammonium perchloia;e (TEAP) (0.1 mol dm-3) in dimethylformamide (DMF) was prepared.…”
Section: Methodsmentioning
confidence: 99%